Gambaran Kesejahteraan Psikologis pada Lansia di Desa Banteran - Alfian Prasetya Yulianto; Asep Iskandar; Lita Heni Kusumawardani (Journal of Applied Science for Pharmaceuticals and Health, 2025)
Background: Changes in organ function in the elderly can hinder interaction with the environment and affect psychological well-being. A supportive environment helps the elderly accept themselves, while a poor environment can trigger depression, stress, and loneliness. Feeling neglected by family can also worsen their psychological condition. This study aimed to identify the psychological well- being of the elderly in Banteran Village. Methodology: This was a descriptive quantitative study with a cross- sectional approach, involving 95 elderly individuals from Banteran Village using simple random sampling. Data were collected through the Psychological Well-Being questionnaire and analyzed using univariate analysis, incorporating the median and minimum-maximum values.. Results: The respondents in this study were elderly individuals aged between 60-73 years, with the most dominant gender being female (65.3%). The results showed that the psychological well-being of the elderly in Banteran Village was low in 44 elderly individuals (46.3%), moderate in 30 elderly individuals (31%), and high in 21 elderly individuals (22.1%). Conclusion: The majority of respondents have low psychological well- being. Therefore, the elderly need social support from their surroundings to improve their well-being.